A review of the monophyly and composition of the Bengaliinae with the description of a new genus and species, and new evidence for the presence of Melanomyinae in the Afrotropical Region (Diptera, Calliphoridae) - Rognes, Knut (Zootaxa, 2011)
Mafikengia ciliata gen. nov., sp. nov. is described from South Africa and assigned to the subfamily Bengaliinae of the Calliphoridae. It is recognisable by its small size (4 mm), mostly yellow body, and a number of peculiar characteristics. The upper end of the bacilliform sclerite is attached to the medial side of the posterior portion of the surstylus on each side, a very unusual feature among calliphorids. This medial connection in Mafikengia is found in all genera of Bengaliinae, but is not present in any other calliphorid subfamily. The monophyly of the Bengaliinae is discussed, the subfamily is diagnosed, the component genera are listed, and a key to the world Bengaliinae is presented. The Bengaliinae are a very well circumscribed group within the Oestroidea, and it is suggested that the status of the subfamily might be raised to the rank of family. A cladistic analysis using NONA shows that Mafikengia is more closely related to the Oriental genus Termitoloemus Baranov, 1936 than to any other genus, and that the tribes Auchmeromyiini and Bengaliini may still be upheldas separate monophyletic groups, but with very low support. The Afrotropical nominal genus Neocordylobia Villeneuve, 1929 is reduced to a synonym of Cordylobia Grünberg, 1903, syn. nov. The nominal species Neocordylobia tauffliebi Zumpt, 1958 is transferred to the genus Tricyclea Wulp, 1885, as Tricyclea tauffliebi (Zumpt), comb. nov. A new interpretation of the male genitalia of Termitoloemus marshalli Baranov is presented. The male genitalia of the Afrotropical species Tricycleala maculipennis Villeneuve as well as the male and female genitalia of the Afrotropical genera Adichosina Villeneuve, Ochromelinda Villeneuve and Onesihoplisa Villeneuve are figured. The uterine first instar larva of the female of Ochromelinda thoracica Villeneuve is described and illustrated. The genera Adichosina, Ochromelinda, Onesihoplisa and Zernyiella Zumpt are assigned to the calliphorid subfamily Melanomyinae on the basis of the morphology of the female ovipositor, male aedeagus and first instar larva. The occurrence of this subfamily in the Afrotropical Region is established for the first time. A lectotype is designated for Zernyiella dubia Zumpt, 1956 to fix the interpretation of the name. Auchmeromyia kurahashi Lehrer, 2005 is established as a junior synonym of Auchmeromyia senegalensis Macquart, 1851, syn. nov. Auchmeromyia pattoniella Lehrer, 2005 is an unavailable name [no type designation] in the synonymy of Auchmeromyia bequaerti Roubaud, 1913. Cordylobia ebadiana Lehrer & Goergen, 2006 is established as a junior synonym of Cordylobia rodhaini Gedoelst, 1910, syn. nov. Pachychoeromyia kanemia Lehrer, 2011 is reduced to a synonym of Pachychoeromyia praegrandis Austen, 1910, syn. nov. The family-group name Coganomyinae of Peris & González-Mora, 2004 is established as a synonym of Bengaliinae Brauer & Bergenstamm, 1889, syn. nov.